Peningkatan Hasil Belajar Matematika Melalui Pembelajaran Quantum Learning Pada Siswa Kelas X SMA Negeri 2 Makassar - Irfawandi Samad (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2017)
Purposed to improve students' mathematics learning outcomes of Class X SMA Negeri 2 Makassar through the implementation of Quantum Learning method. The subjects of this research were 40 students of Class X.4 SMA Negeri 2 Makassar in Even Semester 2014/2015. The first cycle was held 6 times and the second cycle as well. Data retrieval was done by using learning outcome test and observation at each end of the cycles according to the lesson. Based on the results of data analysis obtained that qualitatively, some changes occurred. Students showed enthusiasm to follow the lesson, as well as interest and motivation to learn is improved. While the quantitative increase in the average score of students learning outcomes at the first cycle is 7.16 with a standard deviation is 1.09 to 8.14 with a standard deviation is 0.91 at the second cycle. It means that the result of students’ mathematic learning through the implementation of Quantum Learning method is increased.